2003
DOI: 10.1037/0022-3514.85.5.969
|View full text |Cite
|
Sign up to set email alerts
|

Secure and Defensive High Self-Esteem.

Abstract: Long-standing theories have suggested high self-esteem (SE) can assume qualitatively different forms that are related to defensiveness. The authors explored whether some high-SE individuals are particularly defensive because they harbor negative self-feelings at less conscious levels, indicated by low implicit SE. In Study 1, participants high in explicit SE but low in implicit SE showed the highest levels of narcissism-an indicator of defensiveness. In Studies 2 and 3, the correspondence between implicit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
375
2
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 490 publications
(416 citation statements)
references
References 46 publications
27
375
2
9
Order By: Relevance
“…Furthermore, discrepant implicit-explicit SE in either direction is associated with more dissonance-reducing behaviors. For instance, Jordan and colleagues showed that individuals with high explicit but low implicit SE were more defensive and rationalized their decisions more than those with consistent implicit-explicit SE [29]. As implicit-explicit discrepancies may be associated with anxiety, the present study builds on our previous findings examining the relationship between discrepancies in anxiety and PNES frequency [30].…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, discrepant implicit-explicit SE in either direction is associated with more dissonance-reducing behaviors. For instance, Jordan and colleagues showed that individuals with high explicit but low implicit SE were more defensive and rationalized their decisions more than those with consistent implicit-explicit SE [29]. As implicit-explicit discrepancies may be associated with anxiety, the present study builds on our previous findings examining the relationship between discrepancies in anxiety and PNES frequency [30].…”
Section: Introductionmentioning
confidence: 74%
“…Conflicts between implicit and explicit self-esteem are associated with a number of important psychological problems, such as narcissism (Jordan et al, 2003), self-doubt (Briñol et al, 2006), and maladaptive perfectionism (Zeigler-Hill & Terry, 2007). Future work may investigate whether meditation can alleviate the problems that are associated with discrepancies between implicit and explicit self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, such discrepancies have been associated with distinct psychological disadvantages. For instance, individuals with high explicit self-esteem and low implicit self-esteem are often more narcissistic and vulnerable to criticism than individuals with other configurations of implicit and explicit self-esteem (Bosson, Brown, Zeigler-Hill, & Swann, 2003;Jordan, Spencer, Zanna, Hoshino-Browne, & Correll, 2003;Shröder-Abé, Rudolph, Wiesner, & Schütz, 2007;Zeigler-Hill, 2006). Likewise, individuals with low explicit self-esteem and high implicit self-esteem appear to be especially prone to maladaptive forms of perfectionism (Zeigler-Hill & Terry, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Jordan and colleagues (Jordan, Spencer, & Zanna, 2005; Jordan, Spencer, 368 HOFMANN ET AL. Zanna, Hoshino-Browne, & Correll, 2003) showed that the combination of high explicit self-esteem and low implicit self-esteem is a strong predictor of defensive behaviour such as dissonance reduction, in-group bias, and discrimination. In a similar vein, Brin˜ol, Petty, and Wheeler (2002) demonstrated that people with high discrepancies between implicit and explicit self-conceptions (Studies 1 -3) or self-esteem (Study 4) exhibit a more thorough elaboration of discrepancy-related information than people with small discrepancies, suggesting that highly discrepant people may be motivated to reduce their potentially aversive self-inconsistencies by additional information integration.…”
Section: Implicit -Explicit Consistency 367mentioning
confidence: 99%